Library Book Collection Information System (Case Study: Labuhanbatu University) - Tika Ade Kusuma; Masrizal Masrizal; Irmayanti Irmayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The Labuhanbatu University Library has the goal of supporting information needs, increasing the number of visitors, interest in reading and the number of books borrowed. Every year this library procures a new collection of books, so it is important to know the types of books that are a priority for increasing the number. But currently the library is facing problems in the process of grouping book collections which are still done manually. This process takes a long time and requires high accuracy to avoid errors in grouping books. Therefore, an appropriate solution is needed by utilizing technology to assist librarians in grouping book data quickly and easily. The results of this study succeeded in designing a Book Collection Grouping Information System at the Labuhanbatu University Library. Based on the results of the Blackbox test, it shows that the system created is in accordance with user needs and has successfully passed all the tests carried out, thus indicating that the system can be used by the Labuhanbatu University Library.